2014
DOI: 10.1111/ijcs.12094
|View full text |Cite
|
Sign up to set email alerts
|

Understanding organic food consumption: attitude as a mediator

Abstract: The aim of this research was to examine the effect of health consciousness, environmental concern and food safety concern on both the intention to buy organic foods and the attitude towards organic foods, and the effect of attitude towards organic foods on the intention to buy organic foods. It had also a specific aim to explore whether attitude has a mediation effect on the relationship between the intention to buy and health consciousness, environmental concern and food safety concern. Data were gathered fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
74
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 33 publications
25
74
2
7
Order By: Relevance
“…It is important to note that our research results are different from those of other studies that propose a positive association between healthconsciousness and attitude towards organic food (Ç abuk et al, 2014;Chen, 2009). This difference can be explained by the research results of Wandel and Bugge (1997), which show a contrast between young adults and old adults in the choice of organic food products.…”
Section: Conclusion and Discussioncontrasting
confidence: 99%
“…It is important to note that our research results are different from those of other studies that propose a positive association between healthconsciousness and attitude towards organic food (Ç abuk et al, 2014;Chen, 2009). This difference can be explained by the research results of Wandel and Bugge (1997), which show a contrast between young adults and old adults in the choice of organic food products.…”
Section: Conclusion and Discussioncontrasting
confidence: 99%
“…These results are consistent with those found in several other studies in which the largest proportion of consumers of organic food found in street and organic markets are women (Çabuk et al, 2014;Chen et al, 2014;Mohamada et al, 2014;Van Loo et al, 2014;Wu et al, 2014).…”
Section: Analysis Of the Socioeconomic Characteristics Of Each Groupsupporting
confidence: 93%
“…This factor explains 16.269% of the variance. This finding is also supporting the existing literature as health is the main motivator of consuming organic food (Pellegrini & Farinello, 2009;Lockie et al, 2002;Magnusson et al, 2003;Chryssohoidis & Krystallis, 2005;Gracia & Magistris, 2008;Hughner et al, 2007;Li et al, 2007;Wier et al, 2008;Zepeda & Deal, 2009;Bellows et al, 2010;Cerjak et al, 2010;Hasançebi, 2010;Ergin & Ozsacmaci, 2011;Çabuk et al 2014). The second factor contains three items and it is named as "Product Related" factor which is related to perceived characteristics of organic foods by consumers.…”
Section: Research Findingssupporting
confidence: 85%